The enteric toxicity of gluten enhances graft-versus-host disease after allogeneic hematopoietic stem cell transplantation. (July 2017) - Neuman, Taylor; David, Kevin; Cooper, Dennis; Strair, Roger
Abstract: Pro-inflammatory peptides present in wheat and related grains are associated with celiac disease and non-celiac gluten sensitivity. We hypothesize that these peptides induce enteric responses that may exacerbate the gastrointestinal manifestations of graft-versus-host disease after an allogeneic hematopoietic stem cell transplant. Therefore, we propose that a gluten free diet should be tested as a prophylactic and/or therapeutic intervention against gastrointestinal graft-versus-host disease for patients undergoing an allogeneic hematopoietic stem cell transplant.